(untitled) (Bioagro, 2024)
Embryogenic suspensions constitute a culture system with great practical utility as it presents high multiplication rates and allows culture automatization and synchronization. In guava, somatic embryogenesis has been initiated from different explants of juvenile origin. Although proliferation of embryogenic cultures has been successfully carried out in semisolid medium, using of embryogenic suspensions has not been reported. In this work, establishment of guava (Psidium guajava L.) embryogenic suspensions has been investigated by analyzing the effect of culture medium and different inoculum densities. For guava embryogenic suspensions, MS medium with macronutrients at half strength (MSm) was more appropriate than WPM medium. Better culture aspect was observed in this medium, although no significant differences were found related to growth rate, estimated by settled cell volume (SCV) variation. In relation to inoculum density, even though a density 2.5 % resulted in a lower SCV values at the end of the culture period, it gave rise to higher dry matter accumulation than higher inoculum densities. This work demonstrates the possibility of using suspensions for proliferation of guava embryogenic tissues, and initiation in MSm medium with an inoculum density of 2.5 % SCV and subculturing every 28 days may be recommended to enhance multiplication of cells and embryogenic aggregates.